Marketing Mix Vs Loyalitas Pasien: Studi Literatur - Junaidi, M. Andri; Sulistiadi, Wahyu (UI Scholars Hub, 2020)
Marketing is the entire activity and process of making, communicating, delivering, offering something feasible for customers, clients, co-workers and society in general. The relationship with the hospital, because the hospital is classified as a semi-business organization. Hospitals must use marketing to face all the problems that exist and take all opportunities in order to survive, one of which is the marketing mix. The method used in this paper is a literature review using PRISMA. This resulted in 13 journals, both domestic and foreign. The marketing mix is needed as a way of marketing the hospital. From the search results, it was found that the components of the marketing mix consist of: product (product), place (location), price (price), promotion (promotion), people (people associated with services), process (service process), and physical evidence (physical evidence) has an effect on patient loyalty to the hospital. Although the single component has no effect on patient loyalty, from all the journals reviewed here, simultaneously all components of the marketing mix have a significant effect on patient loyalty after the Annova (F) test is performed.